Islamic Boarding School Program as a Means of Improving Reading and Memorization of the Al-Qur'an for SD IT An-Najah Aceh Tengah Students - Ramadhan Maulana; Muhammad ade hermawan; Muhammad Ridha; Daryanto Setiawan; Muhammad Fauzan; Fajar ahmad lazuardi (As-sunnah: Jurnal Pengabdian Masyarakat, 2023)
Aceh Tengah, Takengon, is an area with a majority Muslim population. The problem that occurs in today's young generation is that many children are not fluent in reading the Qur'an and make many mistakes in reading it in terms of makharijul letters, tajwid, and the length of the reading. Therefore, the implementation of the boarding school program at one of the educational institutions in Takengon is expected to be a medium for children to improve how to read the Qur'an. Then increase their memorization after attending the boarding school program conducted by students of STAI As-Sunnah. The method used in research is CBR (Community Base Research). Community Base Research is research with a collaborative pattern between the community and the world of action-oriented education with service learning to support social movements. The result of this activity was a change in the quality of reading and memorizing the Qur'an of the students of SDIT An-Najah, when reading and memorizing the Qur'an, they became smoother and following the rules of tajwid and makharijul letters. With this activity, it seems that the community is very enthusiastic and enthusiastic, with them fully supporting this activity and their children, who are also very enthusiastic about learning.